Use of preventive measures, beliefs and information received about COVID-19 and their effects on mental health, in two stages of the pandemic in Colombia - Juan Gómez-Salgado; Fredy Pomares-Herrera; Javier Fagundo-Rivera; Mónica Ortega-Moreno; Juan Jesús García-Iglesias; Carlos Ruiz-Frutos (Annals of Medicine, 2022)
Background Several studies have highlighted the effects of the COVID-19 pandemic on both physical and mental health. The aim of this study is to analyse the effects on mental health in two phases of the COVID-19 pandemic (April 2020 and February 2021) in the population of Colombia.Methods Observational, prospective, cross-sectional study along two periods, April 2020 and February 2021. The sample (N = 1309) was extracted from the Colombian population, only including individuals over the age of 18 and residing in Colombia during the pandemic. The IMPACTCOVID-19 questionnaire was used, previously validated in Spain and cross-culturally adapted to the Colombian population, which included sociodemographic data, use of preventive measures, information received and the Goldberg General Health Questionnaire (GHQ-12) for psychological distress (PD). Participants had to sign an informed consent before taking part in the investigation.Results A higher level of PD was observed among women (M = 3.99, SD = 3.39) (p < .001), in those who lived without a partner (M = 3.83, SD = 3.47) (p = .036), and in those with a worse perception of health (M = 6.27, SD = 3.51) (p < .001). PD decreased in the second period from M = 3.99 (SD = 3.36) to M = 2.98 (SD = 3.30) (p < .001), coinciding with a higher use of preventive measures, less distress caused by COVID-19 and greater confidence in healthcare professionals and clinical structures. In the second period, the time spent in getting informed decreased, but the sources of information were the same, principally social media and official sources.Conclusions Better information on the effects and preventive measures to prevent the pandemic improves confidence in the health system and its professionals, reducing the level of PD. There is a need for quality information on social networks and an adaptation of telemedicine to address the pandemic effects on mental health.Key messagesPsychological distress (PD) decreased in February 2021, as compared to April 2020, due to a greater use of preventive measures against COVID-19, and the confidence on the recommendations made by health officials and professionals.Higher PD has been found in women and people who lived without a partner, in line with studies performed in other countries.The accessibility to quality information on the pandemic should be promoted by the Official Health Authorities, thus counteracting data that could be classified as “fake news”.